A spray drying approach for the synthesis of a Na2C6H2O4/CNT nanocomposite anode for sodium-ion batteries. Issue 25 (7th July 2015) - Wu, Xiaoyan; Ma, Jie; Ma, Qidi; Xu, Shuyin; Hu, Yong-Sheng; Sun, Young; Li, Hong; Chen, Liquan; Huang, Xuejie
<x xml:space="preserve">Abstract</x> Sodium-ion batteries have attracted extensive attention for large-scale energy storage applications for renewable energy and smart grids owing to their abundant sodium resources and potential low cost.